EN Job Involvement Influences toward Employee Performances through Job Satisfactions and Organizational Commitments in Sumber Karya Barutama Trans, Co. Ltd - Bagus Rio Prasetya Wardhana (Universitas Muhammadiyah Metro, 2021)
This research aims to analyze influences of job involvement, satisfaction, and organizational commitment toward job satisfaction, organizational commitment and employee performance. This research uses quantitative approach. Samples taken in this research are the employees of Sumber Karya Barutama Trans, Co. Ltd as 96 people taken by using purposive sampling technique. Data collection was taken by spreading questionnaires. The data analysis technique used SEM by PLS program. This research show that: (1) job involvement has significant and positive influences toward employee job satisfaction; (2) job involvement has significant and positive influences toward organizational commitment; (3) job satisfaction does not have significant influences toward employee performance; (4) organizational commitment has significant influences toward employee performance; (5) job satisfaction has significant influences toward organizational commitment; (6) job involvement does not have significant influences toward employee performance.